PELATIHAN KEWIRAUSAHAAN SYARIAH MELALUI PENGOLAHAN KULINER BERBAHAN DASAR IKAN PADA PEREMPUAN PANTAI JAGU - Rahmawati; Badriah (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
Jagu Beach, Kampung Jawa, Lhokseumawe City is a slum area located on the coast. The problem of poverty on the beach which is very famous for the city of Petro Dollar is very ironic. This study collaborated with the extension group of the Ministry of Religion of Lhokseumawe City, all of which amounted to 5 people. The purpose of this service is to provide entrepreneurship training to women on the coast of Jagu City, Lhokseumawe City, which is somewhat more productive to improve the standard of living of the family. This training uses a workshop method where every woman in the area is taught entrepreneurship for souvenirs typical of the city of lhokseumawe made from fish and is taught how the principles of sharia entrepreneurship are taught. The results obtained by women on the coast of Jagu, Lhokseumawe City already have the ability to manage fish-based cuisine, fish obtained from the results of the fishermen around are processed in the form of fish skin crackers and fish dim sum and others. The result of this training is that the women who have been selling along the coast of Jagu started trying to sell fish-based culinary delights such as fish skin, fish sausage, fish dimsum and fish balls.